Illicit arms transfers to Africa and the prominence of the former Soviet bloc: a social network analysis - Kinsella, David Todd (Crime, law and social change, 2014)
Small arms and light weapons are the primary causes of death in the violent conflicts raging today. Although the small arms trade is difficult to track, and the illicit trade doubly so, a wealth of information is available. This article applies some basic tools of social network analysis (SNA) to reveal the high profile of former Soviet bloc countries in the illicit arms trade with Africa. I set up this analysis with a discussion of the features of social networks that allow them to facilitate the transfer of illicit weaponry, and follow the presentation of my findings with some explanations for the prominence of Russia and other post-communist countries in this trade. My discussion focuses on the importance of relationships, their quantity and quality, as providing opportunities for, and constraints on, the flow of material and social resources between the actors and locales that comprise the illicit arms trade network. I also highlight the extent to which the positions of key players may account for their power within the network and their roles in security governance, which in the illicit context requires the maintenance of secrecy and redundancy.